(6y-7)=-1

Simple and best practice solution for (6y-7)=-1 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (6y-7)=-1 equation:


Simplifying
(6y + -7) = -1

Reorder the terms:
(-7 + 6y) = -1

Remove parenthesis around (-7 + 6y)
-7 + 6y = -1

Solving
-7 + 6y = -1

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '7' to each side of the equation.
-7 + 7 + 6y = -1 + 7

Combine like terms: -7 + 7 = 0
0 + 6y = -1 + 7
6y = -1 + 7

Combine like terms: -1 + 7 = 6
6y = 6

Divide each side by '6'.
y = 1

Simplifying
y = 1

See similar equations:

| 8(1/4x-1/4) | | -82=5x-2 | | -6=-n | | 18q-19=12-18+19q | | 2x-6x-6=90 | | -6=n | | 4+4k=-8+k | | -300=-20p | | (4t-8)=20 | | -8n-5n=26 | | 20=-n+6n | | p=15-3Qs | | 910x-12=23 | | -13z+2=-14z+20 | | 24/4x3 | | 2(r+1)-r=-2+4 | | 103x+34=52 | | -3y+4=10 | | .87/1 | | 9/2z-7/3=41/6 | | -5-5j=-4j | | K-14=-18 | | -54=16x+312 | | 4(x+5)=3(x-11) | | (5h+2)=-8 | | 3g-8=-2+2g-10 | | 25=x-16 | | -3h+12=-7h-9-16 | | 9(x-14)=35-7(x+5) | | 24x•35y/25x | | (b+9)=2 | | 14.4=-2.7x-1.8 |

Equations solver categories